Modeling and Jitter Suppression Analysis of a Lifting Multistage Hydraulic Cylinder. Issue 5 (February 2020) - Luo, Chunlei; Ling, Chunlai; Luo, Daming
Abstract: In view of the abnormal phenomena in the movement of the 4-stage hydraulic cylinder, this paper establishes the basic motion model of the multi-stage hydraulic cylinder by melting point nodal cavity method, and analyses the variation law of its external load. On this basis, the erection process of the multi-stage hydraulic cylinder is simulated and analyzed by AMESim, and it is found that the sudden change of pressure at the change of the stage will cause the vibration of the multi-stage. Found that the abnormal vibration of the third piston occurs during the retraction process of the hydraulic cylinder, which is caused by the insufficient guide distance of the 3 stage piston of the multi-stage hydraulic cylinder. The sealing conditions of the piston and the guide sleeve are improved by increasing the guide length of the piston appropriately, and the correctness of the improved scheme is verified by the way of simulation, that is, it can effectively suppress the vibration of the third piston. Vibration occurs during retraction. Some improvement suggestions are provided for vibration reduction of multi-stage hydraulic cylinder.